IMPLEMENTASI Q.S AT-TAHRIM (66) : 6 TERHADAP ORANG TUA SEBAGAI FUNGSI KONTROL DALAM KELUARGA - Nurcahyo, Imam (El-Izdiwaj: Indonesian Journal of Civil and Islamic Family Law, 2020)
Abstract : Implementation of Q.S At-Tahrim (66) : 6 Toward Parents As function of  Control in Family. Marriage is one of muamala’s that has value of worship beside of Allah Swt. which done by male and female. Through the marriage was created family, where the family was one of important regulation in human life. The family who consist of husband, wife and child. Husband and wife in family have role as parents of children all at once. Parents take control in family, the pupose is to give direction for family member to keep consistence in values of Islam. this is what to be said parents as function of control. Also related of Allah Swt say’s in Q.S At-Tahrim (66) : 6 to keep protect member of family or itself from torture of hellfire. It’s related with function of control in family. Because of that the writer want to discuss about implementation of Q.S At-Tahrim (66) : 6 toward parents as function of  control in family.